2017
DOI: 10.3390/cells6040048
|View full text |Cite
|
Sign up to set email alerts
|

Differential Location and Distribution of Hepatic Immune Cells

Abstract: The liver is one of the main organs in the body, performing several metabolic and immunological functions that are indispensable to the organism. The liver is strategically positioned in the abdominal cavity between the intestine and the systemic circulation. Due to its location, the liver is continually exposed to nutritional insults, microbiota products from the intestinal tract, and to toxic substances. Hepatocytes are the major functional constituents of the hepatic lobes, and perform most of the liver’s s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 153 publications
1
63
0
Order By: Relevance
“…Because microvesicles are increasingly recognized as endogenous carriers of microRNAs (39) and macrophages and neutrophils are within close vicinity in the hepatic sinusoids (40)(41)(42)(43), we assessed the presence of CD177 in hepatic macrophages of WT, miR-223 -/-, and anti-Ly6G mAb-treated mice during SRLI by staining with an anti-CD177 antibody to verify whether a neutrophil-mediated delivery could be the source of the miR-223 increase we found in hepatic macrophages of non-neutrophildepleted mice during SRLI ( Figure 5A). The total number of anti- (96 hours) after a 1-week course of CCL4 gavage ( Figure 7A); CCL4-treated miR-223 -/mice infused with miR-223 -/y Neu represented the inflammation controls, while those infused with PBS served as the neutrophil infusion control group.…”
Section: Resultsmentioning
confidence: 99%
“…Because microvesicles are increasingly recognized as endogenous carriers of microRNAs (39) and macrophages and neutrophils are within close vicinity in the hepatic sinusoids (40)(41)(42)(43), we assessed the presence of CD177 in hepatic macrophages of WT, miR-223 -/-, and anti-Ly6G mAb-treated mice during SRLI by staining with an anti-CD177 antibody to verify whether a neutrophil-mediated delivery could be the source of the miR-223 increase we found in hepatic macrophages of non-neutrophildepleted mice during SRLI ( Figure 5A). The total number of anti- (96 hours) after a 1-week course of CCL4 gavage ( Figure 7A); CCL4-treated miR-223 -/mice infused with miR-223 -/y Neu represented the inflammation controls, while those infused with PBS served as the neutrophil infusion control group.…”
Section: Resultsmentioning
confidence: 99%
“…Our study is the first to show that EAD is associated with bloodstream bacterial infection during the first month after LDLT. Because the liver is located between the mesenteric and systemic circulation systems, and plays a key role in the defense against microbiological products and/or toxins emanating from the intestine [61], it is not surprising that EAD was associated with an increased risk of early postoperative bacteremia. Given the relationship between the development of EAD and early post-transplant infection, we suggest that the risk factors for EAD could serve as therapeutic targets to reduce the infection rate.…”
Section: Discussionmentioning
confidence: 99%
“…Cathepsin D (CTSD), a lysosomal aspartyl protease, is ubiquitously distributed [8] but the liver is one of the organs with the highest levels of CTSD protein [9]. Further, the liver comprises the largest population of macrophages [10], which are known to contain high levels of lysosomal enzymes, including CTSD [11,12]. Recently, it has been demonstrated that plasma CTSD is negatively associated with insulin sensitivity, suggesting a link between plasma CTSD and insulin sensitivity [13,14].…”
Section: Introductionmentioning
confidence: 99%